Strategy to Improving Smallholder Coffee Farmers Productivity - Sarirahayu, Kartika; Aprianingsih, Atik (The Asian Journal of Technology Management (AJTM), 2018)
Abstract: Coffee is a leading export commodity that provides great foreign exchange for Indonesia. The increase in domestic coffee consumption and the high export demand apparently cannot be fulfilled by Indonesian coffee producers. Many factors are cause underdevelopment of Indonesia's coffee industry. This paper aims to explore strategies to improve smallholder coffee farmer’s productivity. To understand the phenomenon, author identify the problems encountered in coffee farming. Furthermore, a more in-depth literature review of these issues was conducted to present the most appropriate strategies. Based on the findings, author propose several notions that have positive impact to improving smallholder coffee farmers productivity in Indonesia, there are fair trade certification, technology adoption and intensive farmer training, closely involve women, and focus on active farmers.Keywords: Coffee, technology adoption, empowerment, farmers, Indonesia